Transformasi Melalui Keteladanan : Gaya Kepemimpinan Yesus dalam Manajemen Pendidikan Kristen - Yuwita Despriyantie; Sirnawati Sirnawati; Sepri Sepri; Sarmauli Sarmauli (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This study reveals the power of Jesus' leadership style in Christian education, highlighting the principles of exemplary, service, and sacrifice as the main pillars for creating a conducive learning environment. The results of the study indicate that the implementation of Jesus' leadership model has a positive impact on the formation of spiritual and ethical character of students and staff. It is recommended that Christian educational institutions develop leadership training programs that integrate Jesus' values ​​with modern managerial competencies, and implement a comprehensive evaluation system and mentoring mechanism. Thus, Christian education can be a strong medium for forming character and developing the spirituality of the next generation, emulating the Great Teacher in realizing His mission in the world.